2016
DOI: 10.1590/0103-6440201600733
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polymerization Cycles on Gloss, Roughness, Hardness and Impact Strength of Acrylic Resins

Abstract: The aim of this study was to evaluate the conventional and boiled polymerization cycles on gloss, roughness, hardness and impact strength of acrylic resins. Samples were made for each Classico and QC-20 materials (n=10) in dental stone molds obtained from rectangular metallic matrices embedded in metallic flasks. The powder-liquid ratio and manipulation of the acrylic resins' were accomplished according to manufacturers' instructions and the resins were conventionally packed in metallic flasks. After polymeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 19 publications
(22 reference statements)
1
38
1
8
Order By: Relevance
“…It is difficult to understand and explain because resins fabricated by the same manufacturer (microwaved Onda Crylx conventional Classico, and conventional Vipi Cril Plus x microwaved Vipi Wave x conventional Vipi Characterized) showed different results when submitted to the same disinfection cycles by microwave irradiation, and also when each resin was evaluated among different microwave cycles. Differently from the current results, the literaturs has shown that conventional and boiled polymerization methods promoted similar roughnesses on the QC-20 and Classico acrylic resins; however, the roughness levels for both resins were higher [24].…”
Section: Open Access Http://scidocorg/ijdosphpcontrasting
confidence: 99%
See 1 more Smart Citation
“…It is difficult to understand and explain because resins fabricated by the same manufacturer (microwaved Onda Crylx conventional Classico, and conventional Vipi Cril Plus x microwaved Vipi Wave x conventional Vipi Characterized) showed different results when submitted to the same disinfection cycles by microwave irradiation, and also when each resin was evaluated among different microwave cycles. Differently from the current results, the literaturs has shown that conventional and boiled polymerization methods promoted similar roughnesses on the QC-20 and Classico acrylic resins; however, the roughness levels for both resins were higher [24].…”
Section: Open Access Http://scidocorg/ijdosphpcontrasting
confidence: 99%
“…This result is in agreement with the previous study that reported hardness decrease for acrylic resins after microwave irradiation, but no effect was observed on the impact and flexural strength [16]. Moreover, conventional and boiled polymerization cycles promoted similar roughness and surface hardness for QC-20 and Classico resins [24]; however, the hardness levels for both resins were lesser than those seen in the current study. Based on these results, it is possible to presume smaller rigidity of the resins with the increase of the microwave cycles, which seems to confirm the decrease of the Knoop hardness after repeated microwave disinfections [17], after thermal cycling and disinfection procedures [28], and under effect of different polymerization cycles and water storage [29].…”
Section: Open Access Http://scidocorg/ijdosphpsupporting
confidence: 92%
“…It has been reported that resins with high Ra values displayed higher numbers of Candida albicans specimens in comparison to highly polished smooth surfaces, possibly due to the increased hills and peaks of the rougher surfaces, which provide a wide surface area and are more accessible active sites for microbial adhesion (Verran and Maryan, 1997;Radford et al, 1998). Lower surface roughness is important to prevent stain catching (Consani et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Hardness is important in preventing abrasion and wearing of the PMMA denture base (Consani et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Wax plate (65 mm long, 5 mm wide and 2 mm high in dimensions) (10) were prepared and fixed into flask. Plaster slurry was prepared and poured in the lower half of flask.…”
Section: Heat Cure Acrylic Samples Preparationmentioning
confidence: 99%